Developing Cultural Tourism in Vietnam - Nhung, Nguyen Thi; Dung, Vu Dinh (Journal of Ecohumanism, 2025)
Vietnam is recognized with more than 40000 historical and cultural relics, including more than 3600 national relics. This is a potential factor, creating an advantage for Vietnam to develop cultural tourism. In the current development process, Vietnam is focusing on developing cultural tourism as an important content of the tourism development strategy. Localities in Vietnam all evaluate heritage values ​​and implement programs and plans to exploit and promote cultural heritage values ​​in a suitable manner for socio-economic development. Many localities have been successful in exploiting diverse cultural tourism products, becoming a competitive advantage for development, especially some localities with many famous landscapes, capitals, ancient capitals, etc. In this study, the author focuses on analyzing the practical development of cultural tourism in Vietnam based on a practical survey in the ancient capital of Ninh Binh - a place with many famous landscapes and cultural heritages, with a history of development as the capital of Vietnam in the 10th century; the uniqueness and cultural diversity of Ninh Binh province plays a major role and influence on the economic and social development of the locality and of Vietnam. The research results also assess the factors affecting the development of cultural tourism in Ninh Binh province, thereby discussing and researching related policy issues.